Pancasila's Economic Existence in Business Development: The Efforts to Realize Justice in Business Law - Asmah, Asmah; Azizah, Azizah; Dewi, Retno Sari; Chansrakaeo , Ruetaitip (Magister of Law, Faculty of Law, University of Mataram, 2023)
The Pancasila economy as a characteristic of Indonesia's unique economy encounters problems when faced with increasingly massive business developments. Business law has a role so that the existence of the Pancasila economy is maintained in the era of business development. This study aims to analyze the existence of Pancasila during business development to realize justice in the realm of business law. This is because the Pancasila economy seeks to apply the economic values of Pancasila in accordance with the interpretation of the constitution. This research is normative legal research with conceptual, statutory, and philosophical approaches. The results of the study confirm that the existence of the Pancasila economy is urgent to be maintained through various legal policies so that business development does not perpetuate capitalism which can create injustice in business competition. Business law in its development needs to refer to and pay special attention to the Pancasila economy so that existing business practices in Indonesia are in line with Pancasila values.